Differential Responses of Net Ecosystem Exchange of Carbon Dioxide to Light and Temperature between Spring and Neap Tides in Subtropical Mangrove Forests. (8th July 2014) - Li, Qing; Lu, Weizhi; Chen, Hui; Luo, Yiqi; Lin, Guanghui
Abstract : The eddy flux data with field records of tidal water inundation depths of the year 2010 from two mangroves forests in southern China were analyzed to investigate the tidal effect on mangrove carbon cycle. We compared the net ecosystem exchange (NEE) and its responses to light and temperature, respectively, between spring tide and neap tide inundation periods. For the most time of the year 2010, higher daytime NEE values were found during spring tides than during neap tides at both study sites. Regression analysis of daytime NEE to photosynthetically active radiation (PAR) using the Landsberg model showed increased sensitivity of NEE to PAR with higher maximum photosynthetic rate during spring tides than neap tides. In contrast, the light compensation points acquired from the regression function of the Landsberg model were smaller during spring tides than neap tides in most months. The dependence of nighttime NEE on soil temperature was lower under spring tide than under neap tides. All these results above indicated that ecosystem carbon uptake rates of mangrove forests were strengthened, while ecosystem respirations were inhibited during spring tides in comparison with those during neap tides, which needs to be considered in modeling mangrove ecosystem carbon cycle under future sea level rise scenarios.